In-plane porous Ti3C2Tx sheet and construction method thereof
The in-plane pores are constructed on Ti3C2Tx sheets through Cu2+-induced in-situ etching technology, which solves the problem of limited sheet stacking and vertical ion transport, and significantly improves the ion transmission efficiency and electrochemical energy storage performance of the material.
Patent Information
- Application Number
- CN202510412362.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-03
AI Technical Summary
During the preparation process, Ti3C2Tx sheets have problems such as stacking of sheets and restricted vertical ion transport, resulting in a decrease in effective specific surface area and a sharp attenuation of power.
Through Cu2+-induced in situ etching strategy, uniform in-plane pores were constructed on Ti3C2Tx sheets to form horizontal and vertical interleaved ion transport channels.
It has achieved efficient ion transmission and improved electrochemical energy storage performance of Ti3C2Tx sheets, and is suitable for large-scale production and industrial applications.
Smart Images

Figure CN119911907A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbide two-dimensional materials, and specifically relates to an in-plane porous Ti3C2T x Thin sheets and methods of constructing the same. Background Art
[0002] Ti3C2T x Two-dimensional layered materials have high conductivity, abundant surface functional groups, and tunable interlayer spacing, which make them show great potential in the field of electrochemical energy storage. x There are several key issues in the preparation of thin films. First, the stacking of the layers. x Nanosheets are prone to close stacking due to van der Waals forces and hydrogen bonding, resulting in insufficient exposure of active sites, reduced effective specific surface area, and limited ion adsorption and charge storage capacity. Secondly, vertical ion transport is limited. Traditional Ti3C2T x The thin film lacks an effective pore structure in the vertical direction, and ions need to diffuse along a tortuous path, resulting in a sharp decay of charge under high current density.
[0003] Traditional modification methods suppress stacking by introducing spacers such as carbon nanotubes and graphene, but this method only optimizes ion transport in the horizontal direction, and there is still a tortuous path problem in the vertical direction. Although traditional chemical etching can expand the interlayer spacing, it is difficult to achieve good results in Ti3C2T x Uniform in-plane pores are formed on the thin film, and the strong acid environment can easily destroy the Ti3C2T x The structural stability of the material is reduced, resulting in a decrease in the mechanical properties of the material and a shortened cycle life. In addition, although the prior art attempts to introduce pores through template methods or redox reactions, these methods are complex and costly, limiting their large-scale application. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides an in-plane porous Ti3C2T x Thin film and its construction method. 2+ Induced in-situ etching strategy in Ti3C2T x Uniform in-plane pores are constructed on the thin sheet, and the preparation process is simple and environmentally friendly, suitable for large-scale production applications.
[0005] The present invention is specifically implemented through the following technical solutions.
[0006] The present invention provides an in-plane porous Ti3C2T x The method for constructing a thin sheet comprises the following steps: Ti3C2T x The colloidal solution was mixed with a copper salt aqueous solution at room temperature and stirred to react. 2+Cooperating with dissolved oxygen in aqueous solution, Ti3C2T x Ti in thin slices 2+ or Ti 3+ Oxidized to TiO2.
[0007] After the reaction is completed, an etchant is added to the reaction solution and stirred to react. The etchant is used to etch away the generated TiO2 to form in-plane pores. After the etching treatment, the obtained solid is dispersed in water after centrifugation and washing.
[0008] Preferably, the copper salt aqueous solution is a CuSO4 aqueous solution, a CuCl2 aqueous solution or a Cu(NO3)2 aqueous solution.
[0009] Preferably, Ti3C2T x The concentration of the colloidal solution is 1.5 mg / mL, the concentration of the copper salt aqueous solution is 0.1 mol / L~0.3 mol / L, and the concentration of Ti3C2T x The volume ratio of the colloidal solution to the copper salt aqueous solution is 2:1.
[0010] Preferably, Ti3C2T x After the colloidal solution and the copper salt aqueous solution are mixed at room temperature, the stirring reaction time is 2 hours to 4 hours to ensure the uniformity and sufficiency of the reaction. Appropriately reducing the reaction time or extending the reaction time can control the size and density of the pores in the surface.
[0011] Preferably, the etchant is an HF aqueous solution with a concentration of 10wt% to 30wt%, and the volume ratio of the HF aqueous solution to the copper salt aqueous solution is 1:2.5. During the reaction, the concentration of the HF solution is controlled at 10wt% to 30wt% to ensure that the Ti3C2T x the overall structure.
[0012] Preferably, the etchant is added and stirred for reaction for 20 minutes to 40 minutes.
[0013] The present invention also provides an in-plane porous Ti3C2T ... x Thin sheet, including horizontal and vertical channels, adjacent Ti3C2T x There are horizontal channels between the layers, and each layer of Ti3C2T x There are pores distributed in the surface, and vertical channels are formed between the layers through the pores.
[0014] like Figure 1 As shown, in Ti3C2T x The mechanism of in-plane pore formation can be understood as follows: 2+ The redox potential of Ti 2+ or Ti 3+Correction, and synergistically with dissolved oxygen in aqueous solution, Ti3C2T x Ti in thin slices 2+ or Ti 3+ Catalytic oxidation to TiO2. Then the TiO2 produced is etched to form Ti3C2T x Uniform pores are left in the surface of the sheet.
[0015] The present invention also provides a self-supporting electrode, which comprises a porous Ti3C2T x The colloidal solution of the flakes is vacuum filtered onto a cellulose membrane and vacuum dried at 30°C to 60°C to obtain a self-supporting electrode. The self-supporting electrode can be directly used as a sodium ion capacitor electrode without adding a conductive agent or a binder.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention is based on Ti3C2T x Cu was introduced into the colloidal solution 2+ , through Cu 2+ The Ti3C2T x Ti in thin slices 2+ or Ti 3+ Catalytic oxidation to TiO2, then using an etchant to dissolve the generated TiO2, in Ti3C2T x By controlling the Cu 2+ With Ti3C2T x The reaction time of the colloidal solution is used to control the Ti3C2T x The size and density of the pores in the thin sheet surface. The method of the present invention is simple, mild in conditions, and can not only form vertically and horizontally interwoven ion transmission channels, but also has strong scalability and economy. The method of the present invention does not require complex templates or high-cost chemical reactions, is suitable for large-scale production, and has high industrial application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The present invention constructs an in-plane porous Ti3C2T x Schematic diagram of the thin film.
[0018] Figure 2 For Ti3C2T in Comparative Example 1 x Transmission electron micrograph of the thin slice.
[0019] Figure 3 (a) is the in-plane porous Ti3C2T prepared in Example 2 x Transmission electron microscope photograph of the thin slice, (b) is the corresponding pore size distribution diagram.
[0020] Figure 4(a) is the in-plane porous Ti3C2T prepared in Example 1 x Transmission electron microscope photograph of the thin slice, (b) is the corresponding pore size distribution diagram.
[0021] Figure 5 (a) is the in-plane porous Ti3C2T prepared in Example 3. x Transmission electron microscope photograph of the thin slice, (b) is the corresponding pore size distribution diagram.
[0022] Figure 6 In the figure, (a) is a constant current charge-discharge curve of the self-supporting electrode prepared from the sample in comparative example 1 at different current densities, and (b) is a constant current charge-discharge curve of the in-plane porous Ti3C2T x Constant current charge and discharge curves of the self-supporting electrode prepared from thin sheets at different current densities.
[0023] Figure 7 In the figure, (a) is a cyclic voltammetry curve of the self-supporting electrode prepared from the sample in comparative example 1 at different scanning rates, and (b) is a cyclic voltammetry curve of the in-plane porous Ti3C2T x Cyclic voltammograms of the self-supporting electrode prepared by thin sheets at different scan rates.
[0024] Figure 8 The electric charge values of the self-supporting electrodes prepared from the samples in Example 1 and Comparative Example 1 at different current densities. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention. The experimental methods and detection methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.
[0026] Example 1 An in-plane porous Ti3C2T x The steps of constructing the slice are as follows: (1) Add 50 mL of 1.5 mg / mL Ti3C2T x The colloidal solution was mixed with 25 mL of a 0.2 mol / L aqueous copper sulfate solution at room temperature, and then stirred with a magnetic stirrer for 3 hours.
[0027] (2) After the reaction, 10 mL of 20 wt% HF aqueous solution was added to the solution in step (1) and stirred for 30 minutes.
[0028] (3) The mixed solution after the reaction in step (2) is centrifuged, and the upper clear liquid is discarded after centrifugation, leaving the bottom solid, and the bottom solid is washed with deionized water for multiple times until the pH value of the washing liquid is neutral. Finally, the solid obtained by centrifugation is redispersed in water to obtain a solution containing in-plane porous Ti3C2T x Colloidal solution of thin sheets.
[0029] Example 2 An in-plane porous Ti3C2T x The steps of constructing the slice are as follows: (1) Add 50 mL of 1.5 mg / mL Ti3C2T x The colloidal solution was mixed with 25 mL of a 0.2 mol / L aqueous copper sulfate solution at room temperature, and then stirred with a magnetic stirrer for 2 hours.
[0030] (2) After the reaction, 10 mL of 20 wt% HF aqueous solution was added to the solution in step (1) and stirred for 30 minutes.
[0031] (3) The mixed solution after the reaction in step (2) is centrifuged, and the upper clear liquid is discarded after centrifugation, leaving the bottom solid, and the bottom solid is washed with deionized water for multiple times until the pH value of the washing liquid is neutral. Finally, the solid obtained by centrifugation is redispersed in water to obtain a solution containing in-plane porous Ti3C2T x Colloidal solution of thin sheets.
[0032] Example 3 An in-plane porous Ti3C2T x The steps of constructing the slice are as follows: (1) Add 50 mL of 1.5 mg / mL Ti3C2T x The colloidal solution was mixed with 25 mL of a 0.2 mol / L copper sulfate aqueous solution at room temperature, and then stirred with a magnetic stirrer for 4 hours.
[0033] (2) After the reaction, 10 mL of 20 wt% HF aqueous solution was added to the solution in step (1) and stirred for 30 minutes.
[0034] (3) The mixed solution after the reaction in step (2) is centrifuged, and the upper clear liquid is discarded after centrifugation, leaving the bottom solid, and the bottom solid is washed with deionized water for multiple times until the pH value of the washing liquid is neutral. Finally, the solid obtained by centrifugation is redispersed in water to obtain a solution containing in-plane porous Ti3C2T x Colloidal solution of thin sheets.
[0035] Comparative Example 1 Untreated Ti3C2T in step (1) of Example 1 xColloidal solution.
[0036] Effect verification: Figure 2 For Ti3C2T in Comparative Example 1 x Transmission electron micrograph of the thin slice.
[0037] Figure 3 (a) is the in-plane porous Ti3C2T prepared in Example 2 x (b) is the corresponding pore size distribution diagram. It can be seen that Ti3C2T x Pores have appeared on the surface, but the pore density and size are significantly lower than those of samples prepared after 3 and 4 hours of reaction. x The diameters of the 200 pores distributed on the thin film are mainly 10nm~40nm, and the pores with a diameter of 15nm~30nm are the majority.
[0038] Figure 4 (a) is the in-plane porous Ti3C2T prepared in Example 1 x Transmission electron microscope photo of the thin slice, (b) is the corresponding pore size distribution diagram. The pore size ranges from 10nm to 80nm. Compared with the Ti3C2T x The pore size of the thin film is further expanded, and the number of pores is also significantly increased. The pore size distribution diagram shows that the diameter of the pores is mainly 10nm~40nm. x and Cu 2+ Reaction time can increase pore density and pore size.
[0039] Figure 5 (a) is the in-plane porous Ti3C2T prepared in Example 3. x (b) is the corresponding pore size distribution diagram. It can be seen that Ti3C2T x The pores on the surface are significantly enlarged, and the pore density is also significantly increased. In addition, many pore structures are enlarged and connected to each other to form a larger pore structure. x The diameters of the 200 pores distributed on the thin film are mainly between 30nm and 170nm, and the pores with a diameter of 30nm to 60nm are the majority.
[0040] Example 4 An in-plane porous Ti3C2T x The steps of constructing the slice are as follows: (1) Add 50 mL of 1.5 mg / mL Ti3C2T xThe colloidal solution was mixed with 25 mL of a 0.1 mol / L CuCl2 aqueous solution at room temperature and stirred with a magnetic stirrer for 3 hours.
[0041] (2) After the reaction, 10 mL of 30 wt% HF aqueous solution was added to the solution in step (1) and stirred for 20 minutes.
[0042] (3) The mixed solution after the reaction in step (2) is centrifuged, and the upper clear liquid is discarded after centrifugation, leaving the bottom solid, and the bottom solid is washed with deionized water for multiple times until the pH value of the washing liquid is neutral. Finally, the solid obtained by centrifugation is redispersed in water to obtain a solution containing in-plane porous Ti3C2T x Colloidal solution of thin sheets.
[0043] Example 5 An in-plane porous Ti3C2T x The steps of constructing the slice are as follows: (1) Add 50 mL of 1.5 mg / mL Ti3C2T x The colloidal solution was mixed with 25 mL of a 0.3 mol / L Cu(NO3)2 aqueous solution. After mixing, the reaction solution was stirred for 3 hours using a magnetic stirrer.
[0044] (2) After the reaction, 10 mL of 10 wt% HF aqueous solution was added to the solution in step (1) and stirred for 40 minutes.
[0045] (3) The mixed solution after the reaction in step (2) is centrifuged, and the upper clear liquid is discarded after centrifugation, leaving the bottom solid, and the bottom solid is washed with deionized water for multiple times until the pH value of the washing liquid is neutral. Finally, the solid obtained by centrifugation is redispersed in water to obtain a solution containing in-plane porous Ti3C2T x Colloidal solution of thin sheets.
[0046] In-plane porous Ti3C2T prepared in Examples 4 and 5 x The pore size of the sheet is between 10 nm and 80 nm, which is similar to that of Example 1.
[0047] The following performance tests are carried out using the sample prepared in Example 1 as an example. x The colloidal solution of the flakes was vacuum filtered onto a cellulose membrane, and then vacuum dried at 50°C for 8 hours to obtain a self-supporting electrode. The sample in Comparative Example 1 was prepared into a self-supporting electrode using the same preparation method. The self-supporting electrode was used as a self-supporting electrode for a sodium ion capacitor without adding a conductive agent or a binder. It was assembled into a sodium ion capacitor: First, the self-supporting electrode, activated carbon electrode, and cellulose diaphragm were cut into 1 cm pieces using a punching machine.2 The discs were used as working electrode, counter electrode and diaphragm respectively. Ag / AgCl was used as reference electrode and 1 mol / L Na2SO4 aqueous solution was used as electrolyte to assemble a sodium ion capacitor.
[0048] Figure 6 In the figure, (a) is a constant current charge-discharge curve of the self-supporting electrode prepared from the sample in comparative example 1 at different current densities, and (b) is a constant current charge-discharge curve of the in-plane porous Ti3C2T x Constant current charge and discharge curves of the self-supporting electrode prepared from thin sheets at different current densities. Figure 7 In the figure, (a) is a cyclic voltammetry curve of the self-supporting electrode prepared from the sample in comparative example 1 at different scanning rates, and (b) is a cyclic voltammetry curve of the in-plane porous Ti3C2T x Cyclic voltammetry curves of self-supporting electrodes prepared from thin sheets at different scan rates. The discharge time of the self-supporting electrode corresponding to Example 1 is longer at the same current density, much higher than that of Comparative Example 1. The self-supporting electrode corresponding to Example 1 has a better sodium ion storage capacity. By calculation, the self-supporting electrode corresponding to Example 1 has a higher discharge time at 2 mA cm -2 When the -3 The high volumetric capacity is much higher than the 306C cm of the self-supporting electrode in Comparative Example 1. -3 , showing a higher power value.
[0049] Figure 8 The electric charge values of the self-supporting electrodes prepared from the samples in Example 1 and Comparative Example 1 at different current densities are shown in Table 1. It is worth noting that when the current density increases to 30 mA cm -2 When the charge of the self-supporting electrode corresponding to Example 1 is still 461.3C cm -3 , which is almost 10 times that of comparative example 1, and has excellent rate performance. x The surface is constructed with in-plane pores to create more direct channels in the vertical direction, reduce the tortuosity of the vertical ion path, and achieve rapid ion diffusion.
[0050] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, they are also intended to be included.
Claims
1. An in-plane porous Ti3C2T x A method for constructing a thin sheet, characterized in that: The following steps are involved: Ti3C2T x The colloidal solution was mixed with a copper salt aqueous solution at room temperature and stirred to react. 2+ Cooperating with dissolved oxygen in aqueous solution, Ti3C2T x Ti in thin slices 2+ or Ti 3+ Oxidized to TiO2; After the reaction is completed, an etchant is added to the solution after the reaction and stirred to react. The etchant is used to etch away the generated TiO2 to form in-plane pores. After centrifugation and washing, the obtained solid is dispersed in water.
2. The in-plane porous Ti3C2T3 according to claim 1 x A method for constructing a thin sheet, characterized in that: The copper salt aqueous solution is a CuSO4 aqueous solution, a CuCl2 aqueous solution or a Cu(NO3)2 aqueous solution.
3. The in-plane porous Ti3C2T3 according to claim 1 x A method for constructing a thin sheet, characterized in that: Ti3C2T x The concentration of the colloidal solution is 1.5 mg / mL, the concentration of the copper salt aqueous solution is 0.1 mol / L~0.3 mol / L, and the concentration of Ti3C2T x The volume ratio of the colloidal solution to the copper salt aqueous solution is 2:
1.
4. The in-plane porous Ti3C2T3 according to claim 1 x A method for constructing a thin sheet, characterized in that: Ti3C2T x After the colloidal solution and the copper salt aqueous solution are mixed at room temperature, the stirring reaction time is 2 hours to 4 hours.
5. The in-plane porous Ti3C2T3 according to claim 3 x A method for constructing a thin sheet, characterized in that: The etchant is an HF aqueous solution with a concentration of 10wt% to 30wt%, and the volume ratio of the HF aqueous solution to the copper salt aqueous solution is 1:2.
5.
6. The in-plane porous Ti3C2T3 according to claim 1 x A method for constructing a thin sheet, characterized in that: The stirring reaction time after adding the etchant is 20 minutes to 40 minutes.
7. The in-plane porous Ti3C2T ... x Thin slices.
8. The in-plane porous Ti3C2T3 according to claim 7 x A sheet, characterized in that Including horizontal channels and vertical channels, adjacent Ti3C2T x There are horizontal channels between the layers, and each layer of Ti3C2T x There are pores distributed in the surface, and vertical channels are formed between the layers through the pores.
Citation Information
Patent Citations
Method for synthesizing two-dimensional ultrathin single-crystal Ti3C2Tx lamella
CN106048711A
Preparation method and application of Bi5O7Br / thin-layer Ti3C2 composite photocatalyst
CN110479336A
Cu(I)-at-Ti3C2TxMXene catalytic material, electrode and application of Cu(I)-at-Ti3C2TxMXene catalytic material and electrode in nitrate radical reduction
CN112206797A
Preparation method of three-dimensional wrinkled titanium carbide xerogel and application of three-dimensional wrinkled titanium carbide xerogel in lithium ion battery negative electrode material
CN114477182A
Preparation method of MXene nanosheet with rich intralaminar mesopores
CN114715892A